Correlation between external respiratory indicators and amino acid composition of blood in athletes - Pavlov, V. A.; Rogov, O. S.; Doronin, A. I. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to identify the role of amino acids in the formation of the specific signs of the structural trace of adaptation.